A comunicação de Papa Francisco no Instagram no contexto multicultural contemporâneo - Oling, Jociane Marchesan (2018)
The development of technology and digital media has given rise to questions and insecurities in human and social relations, especially in the religious environment. However, despite being the oldest method of relationship, the practice of communication continues to be an epistemological phenomenon with great problems throughout the centuries. It is not by chance that the greatest social problems come from a lack of dialogue and adequate communication. In the present work, we will open a discussion on the sphere of human relations through digital media. We will start from the communicative potential of Catholicism indirectly unfolded in the representation of Pope Francis, using the Instagram application as environment. His speech of language, the semiotic perspective and how the platform favors the communication purpose of Jorge Mário Bergoglio, to the point of being considered the greatest religious icon of the present time will be observed. To contextualize the study, a theoretical contribution on secularization, media, church and religious icons, semiotics, cyberculture and the practice of semiotic multiletrations will be adopted. The qualitative method chosen is content analysis of the @franciscus profile on Instagram. Although it is not entirely possible, the communication of Pope Francis in the multicultural context can provide us with an alternative to decipher the riddle of digital interpersonal relations, where each wants to be seen and heard more than to see and hear. Therefore, we hope that this study can contribute to a reflection of the communicative technique in view of the importance it brings to society.